Backmatter (Author Guideline, Copyright Transfer Agreement for Publishing Form) (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2009)
Backmatter (Author Guideline, Copyright Transfer Agreement for Publishing Form)